All Days 1980
DOI: 10.4043/3737-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental And Analytical Studies Of The Elastoplastic Behavior Of Offshore Pipelines During Laying

Abstract: With more and more offshore pipelines being laid in deeper water, the need for larger laying equipment has increased larger barges, stronger tensioners and longer stingers. The primary reason is that, in deeper water, the pipeline is suspended at a steeper liftoff angle, and consequently a longer over bend portion is required between the liftoff point and the welding stations In order to help relieve stress in the pipeline. If the over bend portion can be curved until the plastic region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…11a, based on a similar figure established by Harn et al (2019). The square symbols represent critical strains obtained from various programmes of monotonic bending tests (Reddy (1979), Gresnigt et al (1996), Del Col et al (1998), Dorey et al (2001), Gresnigt and van Foeken (2001), Peters et al (2015) and van Es et al (2016)), as gathered by the authors from publiclyaccessibly literature, as well as the data of van Douwen et al (1974), Bouwkamp (1975), Sherman (1976), Korol (1979) and Kimura et al (1980) as reported by Gresnigt (1985).…”
Section: T3 S4rmentioning
confidence: 99%
“…11a, based on a similar figure established by Harn et al (2019). The square symbols represent critical strains obtained from various programmes of monotonic bending tests (Reddy (1979), Gresnigt et al (1996), Del Col et al (1998), Dorey et al (2001), Gresnigt and van Foeken (2001), Peters et al (2015) and van Es et al (2016)), as gathered by the authors from publiclyaccessibly literature, as well as the data of van Douwen et al (1974), Bouwkamp (1975), Sherman (1976), Korol (1979) and Kimura et al (1980) as reported by Gresnigt (1985).…”
Section: T3 S4rmentioning
confidence: 99%